STRUKTUR KOMUNITAS TUMBUHAN PENUTUP TANAH DI CAGAR ALAM DAN TAMAN WISATA ALAM TELAGA WARNA, PUNCAK, BOGOR - - Triastinurmiatiningsih; Sri Wiedarti (Universitas Pakuan, 2012)
This study aims to determine the species of ground cover plant as well as important value index, the level of species diversity and distribution pattern of ground cover in Nature Reserve and Nature Park of Telaga Warna. This researchÂ used the transect method and data collection were using field observation technique. The area of observation consists of three locations with different altitudes including 1400, 1500 and 1600 m asl. Each location is made of three transects that lengthwise the topography. Each transect consists of 10 sample plots measuring 1 x 1 meter with transects spaced 10 meters. Ground cover plant are found as many as 28 species consisting of 20 families. Based on the Important Value Index/INP, obtained the species that dominates at 1400 m asl is Impatiens chonoceras, while at 1500 and 1600 m asl is Scleria laevis. Based on the index of diversity was found that the level of diversity at each location is currently abundant. Based on the index of dispersion was found that the dispersion patterns of ground cover plant at each location is clumped.Â Keywords:Â ground cover plant, Nature Reserve and Nature Park of Telaga Warna